ANATOMIZATION OF ELECTRO & MAGNETO STATIC & DYNAMIC POTENTIAL UNDER THE ATMOSPHERE OF SCALAR AND VECTOR (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this area, we present and think the properties of such potential outcomes and find that they demonstrate some astounding properties that represent the key parts of electromagnetism, lead regularly to the remarkable theory of relativity, and make prepared for measure field hypotheses. Based on their results from both the SSD and the CoreLok vacuum seal method., the latter method provides a better estimation of air voids in a compacted HMA mix for coarse- and fine-graded mixes with high air voids. The paper deals about anatomization of electro and magneto static and dynamic potential under the atmosphere of scalar and vector.